Slow-Wave Sleep and MRI Markers of Brain Aging in a Community-Based Sample - Baril, Andrée-Ann (Neurology, 2021)
OBJECTIVE: To test the hypothesis that reduced slow-wave sleep, or N3 sleep, which is thought to underlie the restorative functions of sleep, is associated with MRI markers of brain aging, we evaluated this relationship in the community-based Framingham Heart Study Offspring cohort using polysomnography and brain MRI. METHODS: We studied 492 participants (age 58.8 ± 8.8 years, 49.4% male) free of neurological diseases who completed a brain MRI scan and in-home overnight polysomnography to assess slow-wave sleep (absolute duration and percentage of total sleep). Volumes of total brain, total cortical, frontal cortical, subcortical gray matter, hippocampus, and white matter hyperintensities were investigated as a percentage of intracranial volume, and the presence of covert brain infarcts was evaluated. Linear and logistic regression models were adjusted for age, age squared, sex, time interval between polysomnography and MRI (3.3 ± 1.0 years), APOE ε4 carrier status, stroke risk factors, sleeping pill use, body mass index, and depression. RESULTS: Less slow-wave sleep was associated with lower cortical brain volume (absolute duration, β [standard error] = 0.20 [0.08], p = 0.015; percentage, 0.16 [0.08], p = 0.044), lower subcortical brain volume (percentage, 0.03 [0.02], p = 0.034), and higher white matter hyperintensities volume (absolute duration, −0.12 [0.05], p = 0.010; percentage, −0.10 [0.04], p = 0.033). Slow-wave sleep duration was not associated with hippocampal volume or the presence of covert brain infarcts. CONCLUSION: Loss of slow-wave sleep might facilitate accelerated brain aging, as evidence by its association with MRI markers suggestive of brain atrophy and injury. Alternatively, subtle injuries and accelerated aging might reduce the ability of the brain to produce slow-wave sleep.